Pengaruh Struktur Modal Dan Pertumbuhan Perusahaan Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Moderasi - Buhaenah Buhaenah; Ayub Wijayati Sapta Pradana (Journal of Business and Economics Research (JBE), 2022)
This study aims to examine the effect of capital structure and company growth on company value, test capital structure on company value moderated by profitability, and test company growth on company value moderated by profitability. This type of research is quantitative descriptive research. The sample used was 52 companies listed on the Indonesian Sharia Stock Index (ISSI) in 2016-2020 using a sampling technique that is purposive sampling. The data used in this research is secondary data. The data analysis in this study used the classical assumption test and the T MRA (Moderate Regression Analysis) test using the SPSS 24 application. The results showed that capital structure had a negative and significant effect on company value, company growth had no significant positive effect on company value, and profitability could moderate the effect capital structure on company value, and profitability cannot moderate the effect of company growth on company value.